Preventing Stress Among Undergraduate Learners: The Importance of Emotional Intelligence, Resilience, and Emotion Regulation - Thomas, Christopher; Zolkoski, Staci (Frontiers in Education, 2020)
In the current investigation, we examined the association among emotional intelligence, emotional regulation tendencies, resilience, and perceived stress within a sample of undergraduate students. Participants (N = 277, 71% Female, 55% White) completed the Brief Emotional Intelligence Scale, Emotion Regulation Questionnaire, Brief Resilience Scale, and Perceived Stress Scale. Using path analysis techniques, we demonstrated that resilience was a negative predictor of perceived stress. Additionally, our results indicated that the use of cognitive reappraisal exerted an indirect influence on perceived stress through resilience. Finally, the current investigation provided evidence that emotional intelligence exerts an indirect influence on stress through both cognitive reappraisal and resilience. We believe the results of the current understanding expand our understanding of the determinants of effective emotional information processing and have implications for intervention efforts designed to reduce perceived stress within university-based samples.